The controllers as lean leader a novel on changing behavior with a lean cost management system - Sondergelt, Sue Elizabeth (CRC Press, 2012)
This book delineates the differences between cost accounting and cost management. It uses a story format to present a compilation of experiences; some good, some bad, and some humorous. The story follows a fictional manufacturing entity embarking on a Lean change management journey for the second time--having failed at its first attempt at Lean implementation a few years earlier. As the story progresses, readers gain an understanding of what the company will do differently this time around to ensure it doesn't slip backward again as the transformation unfolds.